A system of activities to develop the writing skill through intercultural communication in third year medical students in the University of Medical Sciences of Villa Clara - Pérez Amores, Alfredo (Universidad Central "Marta Abreu" de Las Villas, 2013)
Cuba has become a paradigm of humanism all over the world, as professionals of different spheres have accomplished important missions in a great number of countries of the world. One of the most important missions that professionals from Cuba have accomplished is in the sphere of Medicine. The necessity of preparing professionals of this specialty in the Cuban context to continue to help different peoples of the world, demands from them not only the knowledge of the foreign language, but also to know how to behave when living and sharing their lives with any culture different from theirs, having no contradictions, achieving in such a way a good coexistence which will bring better results in their work. This research has as a research question; how to develop the writing skill in English through intercultural communication of third year Medical students. The aim is that they become better professionals and better people in their future. To achieve this purpose, a system of activities was elaborated to develop students´ writing skill. This thesis consists of three chapters. Chapter 1 sets the theoretical considerations that sustain this thesis. It also includes some concepts which are important to understand the idea of this research work. Chapter 2 deals with the needs that support the design of the system. It characterizes the sample, also the different methods and instruments used and the analysis of the results obtained from the diagnosis. Chapter 3 shows the system of written activities proposed. Finally, conclusions, recommendations, bibliography and annexes are included. Key words: English writing skills, intercultural communication, 3rd year medical studies, system of activities, teaching writing.
Keywords: Intercultural Communication; Health Services; English Writing Skill; Health Professionals; Comunicación; Profesionales de la salud; Intercultural Communication; Health Services; English Writing Skill; Health Professionals; Servicios de salud